Evaluation of highway debris flow hazard based on geomorphic evolution theory coupled with material response rate - Na He; Ruze Han; Guisheng Hu; Zhiquan Yang; Linjuan Xu; Filip Gurkalo (Scientific Reports)
Abstract Assessments of highway feasibility frequently lack the detailed data and geological information necessary to conduct hazard evaluations of debris flows. This study discusses the processes of debris flow development when regional rainfall meets the critical level required for debris flow initiation. It utilizes geomorphic evolution theory and establishes a regional risk assessment matrix for debris flow by combining information about gullies and source sensitivity. Considering the location relationship between the highway and debris flow gullies, a rapid evaluation method for debris flow risk assessment along the G318 highway in Sichuan Province is proposed by modifying the judgment matrix. The four debris flow gullies constructed during the upgrading project in Yajiang County, stretching from the west of the city to the Shearer Bay section, were analyzed via examples. The results show that, among the four selected debris flow gullies, two had medium hazard levels, and two had high hazard levels. The validation results are consistent with the actual results, implying that the evaluation method used in this study is accurate and feasible. This method is suitable for the rapid evaluation of debris flow disaster hazards in the feasibility assessment stage of a highway because it relies on readily available data sources, and the evaluation results are fast and convenient. The highway passes through four debris flow gullies, which directly impact the alignment of this particular section of the geological route and the engineering layout. Based on current specifications, the maximum impact range of a one-time debris flow under the given frequency conditions was calculated using the "rainfall method." The results showed that the maximum impact ranges of a debris flow, occurring once in 100 years, for four gullies would be 9.08 m, 9.09 m, 10.86 m, and 10.08 m. The safe clearance heights of bridges over the four gullies should be 14.58 m, 14.59 m, 16.36 m, and 16.3 m. Additionally, the safety clearance width for all gullies should be 5.0 m.